Voice Handicap Index – A Comparison of Clinician’s Ratings and Self Ratings by Individuals with Dysphonia - Medha Hegde; Achala C; Sapna Bhat (Journal of All India Institute of Speech and Hearing, 1970)
Voice Handicap Index (VHI) is one of the measures of self perception of voice problem. It is a short self report questionnaire which is useful in routine clinical situations for assessing the progress of the disorder and the influence of interventions. Although various studies are done on self ratings by individuals with dysphonia (IWD) on VHI, there is a scarcity of studies on comparison of ratings by clinicians and self ratings by IWD. To compare the ratings between the VHI report of the IWD and that obtained by the clinician for the same patient. 13 IWD ranging in age from 18 to 57 years and 13 normal individuals matched on age and gender were chosen as the subjects. VHI was administered for both the groups and results were analyzed by the researcher. The SLP assessed the voice aspect in a separate assessment. VHI was also administered on the control group. Data was analyzed using Mann-Whitney ‘U’ test, Pearson’s correlation procedure and Wilecoxon Signed Ranks Test. The mean scores were higher in experimental group than those obtained by the control group in all the three sections of the VHI questionnaire. Mann Whitney U test showed high correlation between the scores obtained by the IWD and the clinician. There was no significant difference between the two groups on Wilecoxon Signed Ranks Test. Pearson’s correlation procedure showed that there is a high correlation between the VHI scores of the IWD and the scores of the clinician. These results suggest that clinicians are also reliable respondents in assessing the voice handicap in IWD. It may be concluded that the client’s perception of severity of voice disorder will enable the examiner to give treatment to IWD and to know the treatment efficacy by obtaining the clinician’s opinion on the VHI for individuals with voicedisorders.